2020
DOI: 10.1111/bph.14994
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression and pharmacological modulation of TRPM3 in human sensory neurons

Abstract: Background and Purpose:The transient receptor potential (TRP) ion channel TRPM3 functions as a noxious heat sensor, plays a key role in acute pain sensation and inflammatory hyperalgesia in rodents. Despite its potential as a novel analgesic drug target, little is known about the expression, function and modulation in the humans. Experimental Approach:We studied TRPM3 in freshly isolated human dorsal root ganglion (hDRG) neurons and human stem cell-derived sensory (hSCDS) neurons.Expression was analysed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…The roles of PregS as a regulator of TRPM3 channels in humans have been recently reported, demonstrating the expression of TRPM3 channels in human DRG where PregS also produces calcium influx through these ion channels [132], highlighting the relationship between this neurosteroid and TRPM3 channels in the nocifensive response.…”
Section: Trpm3 Is the Main Target For The Effects Of Pregsmentioning
confidence: 93%
“…The roles of PregS as a regulator of TRPM3 channels in humans have been recently reported, demonstrating the expression of TRPM3 channels in human DRG where PregS also produces calcium influx through these ion channels [132], highlighting the relationship between this neurosteroid and TRPM3 channels in the nocifensive response.…”
Section: Trpm3 Is the Main Target For The Effects Of Pregsmentioning
confidence: 93%
“…TRPM3 is widely expressed in both neuronal and non-neuronal tissue, such as in brain and spinal tissues, retinal (53), pituitary, kidney, and testes (49). Through in situ hybridization and RT-qPCR of TRPM3 mRNA, studies have shown abundant expression in both TG and DRG sensory neurons ( Figure 1) (54). A large majority of TRPM3-expressing neurons are also responsive to capsaicin, demonstrating that it is often co-expressed with TRPV1.…”
Section: Trpm3mentioning
confidence: 99%
“…In addition, TRPM3 is upregulated in inflammatory conditions, which increases the overlap with and the interaction with signaling of TRPV1 and TRPA1 [211]. TRPM3 is found in human sensory neurons [212], and concentrations of volatile anesthetics not exceeding the minimal alveolar concentration by far can act as TRPM3 antagonists [213].…”
Section: Trp Channelsmentioning
confidence: 99%